Pengaruh Persentase Enzim Papain dan Bawang Putih pada Rendemen dan Kualitas VCO (Virgin Coconut Oil) - Munir Putro Prayugo; Ersan Ersan; Febrina Delvitasari (Politeknik Negeri Lampung, 2018)
VCO is an oil produced from coconuts that are treated with no heating, one of them using papain enzyme. Vegetable oil is a compound that is easily hydrolyzed and oxidized to make the quality of oil decline. Garlic is a natural antioxidant that can inhibit the oxidation process. Therefore, a study was conducted to determine the effect of papain and garlic enzymes on the rendement and storage duration of VCO. This study used a factorial randomized block design with the first factor was percentage of papain enzyme (0%, 0,15%, 0,20%, and 0,25% and the second factor was percentage of garlic (0%, 0,5%, and 1 %) with 3 replications. The data of the research were analyzed by variance, followed by LSD test at 5% level. The results showed that the highest VCO rendement was obtained from the treatment of 0,25% papain enzyme. One percent (1%) garlic can maintain the quality of water content, FFA, density, and color of VCO at 3 months storage duration, except aroma. The combination of papain and garlic enzymes resulted in negative effect on rendement and cannot maintain VCO quality at 3 months storage duration.Â Keywords: enzyme papain, garlic, VCO storage